Blood Pressure Load: An Effective Indicator of Systemic Circulation Status in Individuals With Acute Altitude Sickness - Chen, Renzheng; Ye, Xiaowei; Sun, Mengjia; Yang, Jie; Zhang, Jihang; Gao, Xubin; Liu, Chuan; Ke, Jingbin; He, Chunyan; Yuan, Fangzhengyuan; Lv, Hailin; Yang, Yuanqi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute high altitude (HA) exposure results in blood pressure (BP) variations in most subjects. Previous studies have demonstrated that higher BP is potentially correlated with acute mountain sickness (AMS). The BP load may be of clinical significance regarding systemic circulation status. Objectives: This study aimed to examine HA-induced BP changes in patients with AMS compared to those in healthy subjects. Further, we provided clinical information about the relationship between variations in 24-h ambulatory parameters (BP level, BP variability, and BP load) and AMS. Methods: Sixty-nine subjects were enrolled and all participants ascended Litang (4100 m above sea level). They were monitored using a 24-h ambulatory blood pressure device and underwent echocardiography within 24 h of altitude exposure. The 2018 Lake Louise questionnaire was used to evaluate AMS. Results: The AMS group comprised more women than men (15 [65.2%] vs. 13 [28.3%], P<0.001) and fewer smokers (4 [17.4%] vs. 23 [50.0%], P=0.009). The AMS group exhibited significant increases in 24-h BP compared to the non-AMS group (24-h SBP variation: 10.52±6.48 vs. 6.03±9.27 mmHg, P=0.041; 24-h DBP variation: 8.70±4.57 vs. 5.03±4.98 mmHg, P=0.004). The variation of mean 24-h cBPL (cumulative BP load) (mean 24-h cSBPL: 10.58±10.99 vs. 4.02±10.58, P=0.016; 24-h mean cDBPL: 6.03±5.87 vs. 2.89±4.99, P=0.034) was also obviously higher in AMS subjects than in non-AMS subjects after HA exposure. 24-h mean cSBPL variation (OR=1.07, P=0.024) and 24-h mean cDBPL variation (OR=1.14, P=0.034) were independent risk factors of AMS. Moreover, variation of 24-h mean cSBPL showed a good correlation with AMS score (R=0.504, P<0.001). Conclusions: Our study demonstrated that patients with AMS had higher BP and BP load changes after altitude exposure than healthy subjects. Excessive BP load variations were associated with AMS. Thus, BP load could be an effective indicator regarding systemic circulation status of AMS.